Health professionals' knowledge about patient safety: an integrative review - Abreu, Ingrid Moura de; Avelino, Fernanda Valéria Silva Dantas; Mendes, Priscila Martins; Rocha, Daniel de Macedo; Tavares, Ana Paula Mousinho; Carvalho, Igho Leonardo do Nascimento; Pierot, Esteffany Vaz (Revista de Enfermagem da UFPI, 2022)
Objective: To analyze, in the literature, health professionals' knowledge about patient safety. Methods: An integrative review with searches and selection in five electronic databases: MEDLINE, CINAHL, Web of Science, LILACS and BDENF, using controlled and non-controlled descriptors indexed in the DeCS and MESH vocabularies. Primary studies with no time or language restrictions were included, with exclusion of duplicates, editorials, theses and dissertations. For analysis and synthesis purposes, the level of evidence classification based on the Oxford Centre for Evidence-based Medicine recommendations and the descriptive methods was used. Results: Eleven articles with level of evidence 2C and developed in the national and international contexts were selected. The level of general knowledge about patient safety among health professionals was considered low, involving significant limitations in the understanding of concepts and definitions, as well as in the application of theoretical assumptions in the care practice. In the categories investigated, certain variation of this knowledge level was observed. Conclusion: There are important gaps in health professionals' knowledge about patient safety, with the subjects presenting low knowledge levels. Therefore, permanent education stands out as a strategy to promote improvements.